The critical review of the translation of Mullah Sadra's Kitāb al-Mas̲h̲āʿir into English - Abbas Mahdavi; mohamad keivanfar (حکمت اسرا, 2018)
In this article, we review the translation of Mullah Sadra's Kitāb al-Mas̲h̲āʿir; The Book of Metaphysical Penetrations. In this article, in addition to the introduction, we emphasize three basic points. First, we want to show in which cases the translation of the Arabic text into English is explicitly incorrect. The translator, Nasr, in some of the sections for the sake of misunderstanding did not succeed in translation of the Arabic text into English. Second, we will show that the translator has dropped some Arabic phrases and did not translate. Finally, we show that some of the English equations are not appropriate. The method we used in writing this article is to begin by introducing Sadra's Arabic text and related English text. Then, we describe both the Arabic and English text, thereby show difference between the text of Mulla Sadra and the translator. Finally, by getting the proposed translation, we will finish the discussion of that section.